Boardroom centrality and firm performance - Larcker, David F.; So, Eric C.; Wang, Charles C.Y. (Journal of Accounting and Economics, 2013)
Firms with central boards of directors earn superior risk-adjusted stock returns. A long (short) position in the most (least) central firms earns average annual returns of 4.68%. Firms with central boards also experience higher future return-on-assets growth and more positive analyst forecast errors. Return prediction, return-on-assets growth, and analyst errors are concentrated among high growth opportunity firms or firms confronting adverse circumstances, consistent with boardroom connections mattering most for firms standing to benefit most from information and resources exchanged through boardroom networks. Overall, our results suggest that director networks provide economic benefits that are not immediately reflected in stock prices.